2009
DOI: 10.1016/j.labeco.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

You can't always get what you want: The impact of the UK Jobseeker's Allowance

Abstract: In 1996 the UK made major changes to its welfare system for the support of the unemployed with the introduction of the Jobseeker's Allowance. This tightened the work search requirements needed for eligibility for benefit. It resulted in large flows out of claimant status, but, this paper concludes, not into employment. The movement out of claimant status was largest for those with low levels of search activity. But, this paper finds no evidence of increased job search activity as a result of this change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 26 publications
9
75
2
1
Order By: Relevance
“…Somehow differently, Ashenfelter et al (2005) exploit differences in the eligibility criteria of different American states (Connecticut, Massachusetts, Virginia and Tennessee) to conduct an experiment and finds out that stricter search criteria do not affect sensibly the access to benefits. Manning (2009) uses a difference in differences estimations to capture the treatment effect on unemployment duration, using the change of unemployment benefits regulation that happened in UK in 1996: his results indicates that criteria affect the access to claims but stricter criteria discourage workers to effectively meet the search requirement and thus do not facilitate the transition to an employment. Several works have also tried to assess the role of unemployment benefits maximum duration on unemployment duration: Nickell and Layard (1999) gives an assessment of this issue and suggest that benefits duration and unemployment duration are positively correlated.. under different financial stress) may exhibit differences in terms of search effort and of reservation wage and, eventually, in the probability of leaving unemployment.…”
Section: The Unemployment Insurance Schemes In Finland Italy and Polandmentioning
confidence: 99%
“…Somehow differently, Ashenfelter et al (2005) exploit differences in the eligibility criteria of different American states (Connecticut, Massachusetts, Virginia and Tennessee) to conduct an experiment and finds out that stricter search criteria do not affect sensibly the access to benefits. Manning (2009) uses a difference in differences estimations to capture the treatment effect on unemployment duration, using the change of unemployment benefits regulation that happened in UK in 1996: his results indicates that criteria affect the access to claims but stricter criteria discourage workers to effectively meet the search requirement and thus do not facilitate the transition to an employment. Several works have also tried to assess the role of unemployment benefits maximum duration on unemployment duration: Nickell and Layard (1999) gives an assessment of this issue and suggest that benefits duration and unemployment duration are positively correlated.. under different financial stress) may exhibit differences in terms of search effort and of reservation wage and, eventually, in the probability of leaving unemployment.…”
Section: The Unemployment Insurance Schemes In Finland Italy and Polandmentioning
confidence: 99%
“…The impact of higher search requirements on average search intensity is theoretically ambiguous, as some will search more intensively to meet the requirements, while others may consider the requirements too burdensome and give up search (see Manning, 2005), with an ambiguous impact on the exit rate into new jobs. But the introduction of stricter eligibility criteria unambiguously reduces utility during claimant job search, with negative effects on reservation wages and post-unemployment wages, and raises the share of nonclaimants in the nonemployment stock, thus possibly raising the take-up rate of other kinds of benefits and lowering future employment rates.…”
Section: Introductionmentioning
confidence: 99%
“…One central element of these policies is the imposition of work search requirements for single parents who claim benefits, with the aim of increasing the flow into employment. Previous work has shown that work search requirements might induce individuals with low level of labour market attachment to give up search entirely and join the ranks of those not in employment nor on benefits ( Manning, 2009;Petrongolo, 2009 ). This casts doubt on the effectiveness of search conditionalities for single parents, a socio-demographic group that tends to have low levels of labour market participation.…”
Section: Introductionmentioning
confidence: 99%
“…The literature estimating the impact of work search requirements for the unemployed is too large for us to summarise, but two very relevant studies are Manning (2009) and Petrongolo (2009) , which both study the introduction of work search requirements for the unemployed in the UK (with the introduction of Jobseeker's Allowance (JSA) in 1996). Both studies find the JSA reform to have moved people off unemployment benefits, but not into work, with large flows into non-claimant unemployment and benefits for those with disabilities or poor health (we call these "health-related benefits " hereafter).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation